Studies on honeybee foraging and pollination in cardamom (Elettaria cardamomum Maton) - Kumar, O P Chaudhary, Rakesh (Journal of Spices and Aromatic Crops, 2000)
Studies on floral biology, foraging behaviour and honeybee pollination in cardamom (Elettaria cardamomum) were conducted at Kadasikadavu (Idukki District, Kerala, India) during 1993 to 1995. Anthesis commenced around 0500 h and dehiscence occurred at 0600 h. The styles with receptive stigmas emerged at 0900 h and flowers withered after 12-13 h. Apoidea were the predominant flower visitors (more than 99% of all visitors), the Indian hive bee (Apis cerana indica) being the major visitor (95.8%) followed by Trigona iridipennis (2.2%). A. cerana indica foraging for nectar and pollen peaked from’0700 to 0900 anq 0800 to 0900 h, respectively with no bee record after 1300 h. A. cerana indica spent more time collecting nectar (12.4 sec) than pollen (7.4 sec) and the proportion of nectar foragers was more (101.7/day) than pollen gatherers (61.6/day). The number of flower visits was minimum (6.6/min) at 0600 h which increased progressively to 14.9 min at 1100 h. The number of capsules/10 panicles, number of seeds, number of seeds/capsule, seed weight and 1000-seed weight were higher in open pollination than without insect pollination. Bee pollination resulted in better quality capsules of uniform shape and bigger size.